Level of Development of Electronic Services in Poland Compared with the European Union States - Dominiak, Joanna (Quaestiones Geographicae, 2011)
The development of information and telecommunications technology has been a breakthrough in the economy and social life. Both modern and traditional sectors of the economy rely on ICT to manufacture new or much improved products and to modify and improve various types of services, e.g. educational, financial, medical, or administrative. With the propagation of ICT there have appeared new ways of acquiring information, learning, doing shopping, or spending leisure time. Thus, progress in ICT contributes to the formation of a knowledge-based economy and an information society. The chief aim of this article is to analyse the level of development of electronic services in Poland against the backcloth of other European Union states. The following issues will be discussed in more detail: (1) the state of physical infrastructure necessary for the development of e-services in Poland and other EU states, (2) the level of development of selected types of e-services for individual consumers and enterprises in Poland, and (3) a comparison of the level of development of selected types of e-services with other EU states.